Regarding the Problem of Legislative Definition of Labor Legislation’s Competence, the Concept and Features of Labor Relations - V. S. Venediktov; K. Yu. Melnyk (Law and Safety)
The authors have studied the norms of the draft Law of Ukraine “On Amending the Labor Code of Ukraine to Define the Concept of Labor Relations and Features of Their Existence” dated from February 9, 2021 No. 5054. The scholars’ points of view on understanding the competence of labor legislation, concepts and features of labor relations have been studied. The authors have determined the expediency of introducing the norms suggested by the draft Law for inclusion in the Labor Code of Ukraine in relation to the competence of labor legislation, concepts and features of labor relations. Recommendations for solving the identified problems have been formulated.